Types of Speech Strategies in Critical Speech Acts by Urban Society in Indonesian Metropop Novels - Febrianto, Yoko; Manaf, Ngusman Abdul (JOLLT Journal of Languages and Language Teaching, 2025)
Communicating in activities is an activity that can never be separated from human life. Inappropriate communication can make the other person interpret the conversation with a different meaning, including the wrong meaning. The use of critical language must be clarified with its intent. The use of this speech act is carried out not only verbally but also in writing. Thus, in speaking, it is not only found in oral communication but also in written communication, for example novels. Therefore, it is necessary to explain the types of speech strategies in speech acts of criticizing urban society in Indonesian metropop novels. This study is about speech strategies in the form of speech acts criticizing urban society in metropop novels using a mixed method research type. The research instrument is the researcher himself who is equipped with an inventory format, identification, and data classification. The results of this study are that the most common speech strategy found is the strategy of speaking without further ado. Meanwhile, the least is in the strategy of speaking frankly with positive politeness. The implications of this study can be applied in the learning process, namely in the related basic competencies, namely commenting on original or translated youth novel excerpts (KD 14.1) in junior high school class VIII semester two.